Impact of Reward and Punishment on Performance Employees - Amin, Gazali (P3M STIEM BONGAYA, 2021)
The aim of this study is to determine if there is an impact of reward and punishment on the performance of employees at the Directorate General of Customs and Excise Type Madya Pabean B Makassar's supervision and service office. The data used in this study are primary data collected directly via the distribution of questionnaires. This study involved 44 employees of the Directorate General of Customs and Excise Type Madya Pabean B Makassar's Supervision and Service Office. Data analysis techniques using multiple linear regression techniques with the SPSS 24 package. The results indicated that the first suggested hypothesis was accepted because the hypothesis test revealed a positive but negligible result. The second hypothesis was accepted because it yielded positive and statistically valid hypothesis test results.